Fishery Business Development Strategy in Indragiri Hilir Regency, Riau Province - Lathifatul Rosyidah; Mei Dwi Erlina (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Indragiri Hilir Regency has great potential in catch fisheries sector. However, many obstacles and challenges faced by local governments in the development of capture fisheries business, due to various factors. The objectives of this research are: 1) to identify the potential of capture fisheries, ie facilities and infrastructure, and the existing condition 2) to formulate the strategy of developing the capture fishery business. This research used qualitative and quantitative approach. The data collected includes primary and secondary data. Data collection techniques were condusted through in-depth interviews and FGDs with business actors, as well as stakeholders in Indragiri Hilir District equipped with observations and documentations. Data analysis used SWOT method by first analyzed the internal and external factors that produced 3 alternative strategies. These alternatives strategies then re-analyzed using the QSPM analysis unit to determined of priority strategies. The results of this research is the potential of capture fisheries in Indragiri Hilir Regency is very large, but there are still many obstacles due to facilities and infrastructure support is still minimal. Alternative strategies generated in this study are 1). utilization of fisheries and marine resources through improvement of facilities and infrastructure of environmentally friendly fishing units, 2). optimizing the role and function of TPI through PPI development, 3). increasing the role of “Pokmaswas” through the provision and utilization of monitoring facilities.